PENGARUH PENGGUNAAN MODEL GALLERY WALK SEBAGAI MEDIA KOMUNIKASI PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA MAN BATAM - Adealila, Nurul Asti; Abidin, Sholihul (LPPM Universitas Putera Batam, 2020)
The purpose of this research is to study the pattern of the use of the walking gallery as a learning communication medium for student learning interest. Regarding the background of this study, because the Indonesian evaluation system uses different methods in the learning process. So is the cooperative learning model. This type of research is quantitative research using descriptive methods. Descriptive research reconsidering facts, circumstances, variables and phenomena that occurred at that time and presents data that are considered to exist. On the basis of the results of tests conducted by researchers, it turns out the proposed hypothesis can be accepted. Hypothesis testing can show a significant positive effect between media gallery walk (X) on student learning interest (Y). Then Ho is rejected and Ha is accepted. The size of the effect of the pavement model on the size of education (X) on learning interest (Y) can be seen from the coefficient of determination of 0.475. The analysis found that 47.5% of the use of the Walk Gallery learning media towards the learning interests of Man Batam students. Keywords: Communication Media, Gallery Walk, Learning Interest, Learning Media.